LESLIE MARMON SILKO’S CEREMONY: TAYO’S HEALING QUEST - Fattah, Mushtaq Abdulhaleem Mohammed (International Journal of Language and Literary Studies, 2022)
Leslie Marmon Silko is one of the most prodigious Native American writers of the 1970s. She is distinguished for her engagement with folklore traditions, religious inspirations, and quest narratives. In her novel, Ceremony (1977), Silko introduces a man on a journey that is full of hardships and frustrations. Accordingly, the present paper explores Tayo’s journey through which he quests for healing his psychological distress and physical illness caused by the atrocities of World War II. The paper also investigates different kinds of journeys the protagonist, as a war veteran, takes up and the various motives behind them. Finally, the paper tries to answer questions such as “What is the significance of the people the protagonist meets during his healing quest? Is he healed physically and psychologically at the end of the novel? How? Why? How do all the processes of healing contribute to affirming his identity and restoring his humanity?”